2016
DOI: 10.3233/bmr-160683
|View full text |Cite
|
Sign up to set email alerts
|

Kinesio Taping for temporomandibular disorders: Single-blind, randomized, controlled trial of effectiveness

Abstract: In conclusion, KT in combination with counseling and exercise is more effective than counseling and exercise alone in TMDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 16 publications
1
28
0
14
Order By: Relevance
“…Physical therapy is one of the most common conservative interventions for the management of TMD7 and given that the aetiology may be unclear,8 several therapeutic approaches have been described 9. One approach is manual therapy applied to the craniomandibular structures with evidence suggesting a significant reduction in pain with manual therapy treatment,10 although responses are highly variable 11.…”
Section: Introductionmentioning
confidence: 99%
“…Physical therapy is one of the most common conservative interventions for the management of TMD7 and given that the aetiology may be unclear,8 several therapeutic approaches have been described 9. One approach is manual therapy applied to the craniomandibular structures with evidence suggesting a significant reduction in pain with manual therapy treatment,10 although responses are highly variable 11.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the increased clinical application of KT in physiotherapy practice, especially after traumatic injuries, only a few studies investigate the effectiveness of KT in OMS literature; two studies showing effects of KT after maxillofacial trauma, 17 , 19 four studies after impacted tooth surgery, 5 , 15 , 16 , 18 two studies after orthognathic surgery, 20 , 21 and one study for temporomandibular joint disorders. 23 However, the aforementioned studies did not include placebo taping. Thus, the actual efficacy of KT application, distinguished from the placebo effects, on postoperative morbidity after OMS is not clear in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Lietz-Kijak, et al 21 (2018) revealed that KT had beneficial effects on the reduction of facial swelling after orthognathic surgery. Coskun Benlidayi, et al 23 (2016) investigated the efficacy of KT in patients with TMD regarding functional jaw movements, pain scores for joint and masticatory muscles, and depression and disability scores. The authors reported that additional KT application was more effective for treatment of TMDs than counseling and exercise alone.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of studies have been conducted on the efficacy of kinesio taping since its first introduction; it has been reported to have favorable effects in a considerable portion of these studies [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%